2022
DOI: 10.3390/biology11121775
|View full text |Cite
|
Sign up to set email alerts
|

Genomics, Origin and Selection Signals of Loudi Cattle in Central Hunan

Abstract: Due to the geographical, cultural and environmental variability in Xiangxi, China, distinctive indigenous cattle populations have formed. Among them, Loudi cattle and Xiangxi cattle are the local cattle in Hunan, and the environment in Loudi is relatively more enclosed and humid than that in Xiangxi. To study the genome and origin of Loudi cattle in hot and humid environments, 29 individuals were collected and sequenced by whole-genome resequencing. In addition, genomic data were obtained from public databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…The detection of genetic variation, genetic diversity, and population structure showed that local dairy goat breeds are more genetically diverse than imported breeds. Previous studies in cattle ( 37 , 38 ) and sheep ( 17 ) have shown similar results. This phenomenon suggests the local breeds have undergone less intensive selection, which may explain why their milk production performance is not outstanding.…”
Section: Discussionsupporting
confidence: 78%
“…The detection of genetic variation, genetic diversity, and population structure showed that local dairy goat breeds are more genetically diverse than imported breeds. Previous studies in cattle ( 37 , 38 ) and sheep ( 17 ) have shown similar results. This phenomenon suggests the local breeds have undergone less intensive selection, which may explain why their milk production performance is not outstanding.…”
Section: Discussionsupporting
confidence: 78%